File names of the images and videos recorded at the microscope from the Bleaching Ecophysiology Assessment experiment at final observations - Christiane Schmidt; Diana N Puerto Rueda; Moritz Nusser; Clinton A Oakley; Xavier Pochon; Marleen Stuhr; Débora Raposo; Simon K Davy (PANGAEA, 2025)
This dataset contains epifluorescence images of individual foraminifera Sorites orbiculus and Amphistegina lobifera subjected to menthol and control treatments at both initial and final time points of a menthol-DCMU bleaching experiment. Additionally, the dataset includes videos capturing pseudopodial movement at the final time points to assess foraminiferal motility during observation.
In: Schmidt, C et al. (2025): Menthol-DCMU bleaching experiments on two foraminifera species, Amphistegina lobifera and Sorites orbiculus [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974618